\begin{gathered}a) \int{(x^4-8x^3+4x)}dx=\\ | \int{x^{\alpha}dx}= \frac{x^{\alpha+1}}{\alpha+1}+C|\\ = \int{x^4}dx-8\int{x^3}dx+4\int{x^1}dx=\\ = \frac{x^{4+1}}{4+1}-8 \frac{x^{3+1}}{3+1}+4 \frac{x^{1+1}}{1+1}+C=\\ = \frac{x^5}{5}- \frac{8x^4}{4}+ \frac{4x^2}{2}+C=\\ = \frac{x^5}{5}-2x^4+2x^2+c;\\ \end{gathered}a)∫(x4−8x3+4x)dx=∣∫xαdx=α+1xα+1+C∣=∫x4dx−8∫x3dx+4∫x1dx==4+1x4+1−83+1x3+1+41+1x1+1+C==5x5−48x4+24x2+C==5x5−2x4+2x2+c;
\begin{gathered}b) \int{\cos(2x)sin(x)}dx=|d(\cos(x))=-\sin(x)dx|=\\ =-\int{\cos(2x)d(\cos(x))}=\\ |\cos(2\alpha)=\cos^2\alpha-\sin^2\alpha=2\cos^2\alpha-1=1-2\sin^2\alpha|\\ =-\int{(2\cos^2(x)-1)}d(\cos(x))=| t=\cos(x)|=\\ =-\int{(2t^2-1)}dt=|\int{x^{alpha}}dx= \frac{x^{\alpha+1}}{\alpha+1}+C|\\ =-2\int{t^2}dt+\int{t^0}dt=-2 \frac{t^{2+1}}{2+1}+ \frac{t^{0+1}}{0+1}=\\ =- \frac{2}{3}t^3+t+C=|t=\cos(x)|=\cos(x)- \frac{2}{3}\cos^3(x)+C=\\ \cos(x)(1- \frac{2}{3}\cos^2(x))+C=\\ =\cos(x)(1- \frac{2}{3}(1-\sin^2(x))+C= \end{gathered}b)∫cos(2x)sin(x)dx=∣d(cos(x))=−sin(x)dx∣==−∫cos(2x)d(cos(x))=∣cos(2α)=cos2α−sin2α=2cos2α−1=1−2sin2α∣=−∫(2cos2(x)−1)d(cos(x))=∣t=cos(x)∣==−∫(2t2−1)dt=∣∫xalphadx=α+1xα+1+C∣=−2∫t2dt+∫t0dt=−22+1t2+1+0+1t0+1==−32t3+t+C=∣t=cos(x)∣=cos(x)−32cos3(x)+C=cos(x)(1−32cos2(x))+C==cos(x)(1−32(1−sin2(x))+C=
\begin{gathered}=\cos(x)(1- \frac{2}{3}+ \frac{2}{3}\sin^2(x))+C=\\ =\cos(x)( \frac{1}{3}+ \frac{2}{3}\sin^2(x))+C=\\ = \frac{1}{3}\cos(x)(1+2\sin^2(x))+C; \end{gathered}=cos(x)(1−32+32sin2(x))+C==cos(x)(31+32sin2(x))+C==31cos(x)(1+2sin2(x))+C;
\begin{gathered}c)\int(e^{3x}+1)dx=\int{e^{3x}}dx+\int{}dx=\\ |\int{e^x}dx=e^x+C; \int{x^\alpha}dx= \frac{x^{\alpha+1}}{\alpha+1}+C;d(x)= \frac{1}{3}dx|}\\ = \frac{1}{3}\int{e^{3x}}d(3x)+\int{x^0}dx=\\ = \frac{1}{3}e^{3x}+ \frac{x^{0+1}}{0+1}+C=\\ = \frac{1}{3}e^{3x}+x+C \end{gathered}
так так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так так
Пошаговое объяснение:
ак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так так